An Efficiency Study of the Aerodynamic Sound Generators Suitable for Acoustic Particle Agglomeration - Vekteris, V.; Ozarovskis, D.; Moksin, V.; Turla, V.; Jurkonis, E. (Engineering, Technology & Applied Science Research, 2020)
The object of this study is the acoustic field generated by aerodynamic acoustic generators of various types and designs. Six types of aerodynamic acoustic generators were studied experimentally and theoretically to determine the parameters of their generated acoustic field. It was established that the aerodynamic Hartmann type sound generator produces the necessary for acoustic particle agglomeration acoustic field and can be used in acoustic air cleaning equipment. It was established that classical theoretical calculation methods underestimate the design features of aerodynamic acoustic generators and cannot be used to calculate their characteristics.